FEMINISME DALAM NOVEL JUGUN IANFU: JANGAN PANGGIL AKU MIYAKO KARYA E.ROKAJAT ASURA - Suryani, Lilis; Priyadi, Totok; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was conducted inasmuch as the researcher willingness to find study on feminism in a novel entitled Jugun Ianfu: Jangan Panggil Aku Miyako by E. Rokajat Asura. The purpose of this research was to examine the forms of gender injustice of the main characters in Jugun Ianfu: Jangan Panggil Aku Miyako by E. Rokajat Asura and profeminism figures in Jugun Ianfu: Jangan Panggil Aku Miyako by E. Rokajat Asura. The theories used in this research dealed with forms of gender injustice, authority feminsm, socialize feminism and literary criticism approach feminism.The method used in this reaserch was descriptive qualitative with feminist literary criticsm approach. The data resources in this reaserch was a novel entitled Jugun Ianfu: Jangan Panggil Aku Miyako by E. Rokajat Asura. The data collection technique was direct technique through the documenter study. Examination technique of the data validity was trough the adequacy of references and triangulation. The data analysis technique which was applied was describing and interpreting the forms of gender injustice and the forms of profeminism expounded in the words in a novel Jugun Ianfu: Jangan Panggil Aku Miyako by E. Rokajat Asura. Keywsords: Feminism Study, Profeminisme, The Gender Injustice